ECMO combined with IABP for the treatment of fulminant myocarditis caused by the targeted drug entrectinib for lung adenocarcinoma: a case report - Yujuan, Qi; Xiaozhong, Ma; Zhenhua, Wu; Yunpeng, Bai (Frontiers in Cardiovascular Medicine, 2025)
BackgroundEntrectinib, a recently approved multikinase inhibitor indicated for advanced ROS1-positive non-small cell lung cancer (NSCLC), has demonstrated significant survival benefits in metastatic disease. However, it carries risks of severe cardiotoxicity. We report the successful management of entrectinib-induced fulminant myocarditis using integrated venoarterial extracorporeal membrane oxygenation (V-A ECMO) and intra-aortic balloon pump (IABP) circulatory support.Case summaryA 71-year-old male diagnosed with lung adenocarcinoma three years ago (ROS1-positive on genetic testing) initiated crizotinib therapy. One week prior to admission, surveillance chest computed tomography(CT) revealed disease progression with increased tumor burden, prompting transition to entrectinib. Seven days post-treatment initiation, he presented to our emergency department with acute-onset palpitations, dyspnea, dizziness, and nausea. Emergent coronary angiography excluded significant stenosis. The patient subsequently developed frequent ventricular premature complexes(VPCs), cardiogenic shock (serum lactate 2.6 mmol/L), and acute heart failure. Absent cardiac history and negative viral serology supported a diagnosis of drug-induced fulminant myocarditis. V-A ECMO with IABP support was emergently instituted. Remarkable recovery ensued: cardiac function normalized by day 3 (ECMO decannulation), followed by extubation and IABP removal on day 5.After 12 days of hospitalization, the patient was discharged. Ejection fraction (EF) recovered from 10% at admission to 61% at discharge. Follow-up demonstrates sustained cardiac function comparable to discharge status.ConclusionEntrectinib demonstrates potential cardiotoxicity in lung adenocarcinoma therapy, necessitating prospective studies to quantify this risk. During treatment, multidisciplinary team (MDT) collaboration is essential for rigorous cardiac function surveillance. This case establishes V-A ECMO with IABP as an effective salvage therapy for drug-induced fulminant myocarditis.